The Principle of Balance in Employment Agreements at Private Educational Institutions : Study of Employment Agreements at Ruhama Islamic College - Muhammad Imaduddin Zikky; Iwan Erar Joesoef; Suherman Suherman (International Journal of Sociology and Law, 2024)
Based on The 1945 Constitution of the Republic of Indonesia (UUD 1945), especially in the Preamble to the Fourth Paragraph , the State of Indonesia has objective national For advance well-being general and enlightening life nation . This matter become base law for development national focus on improvement​ quality source Power human resources (HR) as the main capital .Education and skills is two element important in creating quality human resources . Article 26 paragraph (2) of the 1945 Constitution confirms that every citizens have the right on education . Article 31 paragraph (3) also states that government responsible answer on maintenance education . This matter show internal state commitment provide access broad and equitable education​ for all over people of Indonesia.